2020
DOI: 10.1101/2020.06.03.132126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Atr-Chek1 pathway inhibits axon regeneration in response to Piezo-dependent mechanosensation

Abstract: 26Atr is a serine/threonine kinase, known to sense single-stranded DNA breaks and activate 27 the DNA damage checkpoint by phosphorylating Chek1, which inhibits Cdc25, causing cell 28 cycle arrest. This pathway has not been implicated in neuroregeneration. We show that in 29 Drosophila sensory neurons, removing Atr or Chek1, or overexpressing Cdc25 promotes 30 regeneration, whereas Atr or Chek1 overexpression, or Cdc25 knockdown impedes 31 regeneration. Inhibiting the Atr-associated checkpoint complex in neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
0
0
0
Order By: Relevance
“…Previous studies [24][25] conducted on Drosophila revealed that the Atr-Chek1 pathway negatively regulated the regeneration of sensory neuron axons and dendrites. More recently, also in Drosophila, the Atr-Chek1 pathway was shown to be activated independently of damaged DNA, but rather by mechanical stimuli mediated by Piezo1 and its downstream NO signaling pathway, leading to the inhibition of axon regeneration [26][27][28] (Fig. 3A).…”
Section: Neuron and Oligodendrocytementioning
confidence: 90%
“…Previous studies [24][25] conducted on Drosophila revealed that the Atr-Chek1 pathway negatively regulated the regeneration of sensory neuron axons and dendrites. More recently, also in Drosophila, the Atr-Chek1 pathway was shown to be activated independently of damaged DNA, but rather by mechanical stimuli mediated by Piezo1 and its downstream NO signaling pathway, leading to the inhibition of axon regeneration [26][27][28] (Fig. 3A).…”
Section: Neuron and Oligodendrocytementioning
confidence: 90%